Pembacaan Surat Al-Waqi’ah dan Ayat-Ayat Rezeki Sebagai Potret Ritual Keagamaan - Mila; Ridya Nur Laily; Mardliyatun Nahdliyah Putri (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2023)
Consistent reading of the holy verses of the Koran by the communities will trigger a religious ritual. Hubbun Nabi Community made the tradition of reading Q.S. al-Waqiah [56] which in general talks about the day of resurrection as a form of ritual to open the door of sustenance. This study aims to find out the objective, expressive and documentary meaning of the recitation of the letter al-Waqi'ah and the verses of sustenance by the Hubbun Nabi Community. This type of research includes field qualitative with a sociology of knowledge approach. The research data comes from observations of the traditions of Hubbun Nabi Community, as well as interviews conducted with the founders and members of the assembly regarding the meaning of tradition. The results of the study show that the objective meaning of the selection of letters and verses read in the practice of Hubbun Nabi Community originates from the KH. Fuad Noerhasan’s massage who gave the full trust for the community. The expressive meaning includes feeling the smoothness of sustenance, the blessings of life, getting inner peace, answering prayers, bringing many virtues and rewards, and increasing Islamic ukhuwah. Meanwhile, the documentary meaning of the existence of Hubbun Nabi Community tradition is that there is a change in mystical-based societal reasoning to become spiritual-qur'ani. This proves that Hubbun Nabi Community succeeded in bringing the Qur'an to life through a religious ritual that instilled strong belief in each of the agens.